"Nonalcoholic Fatty Liver and Metabolic Syndrome in a Population of Southeastern Mexico" - Berenice, Morales Rodríguez; Sandoval Jurado Luis, Jimenez Báez María Valeria; Angel3, Labra Flores Miguel; Rene, Pesqueda González; Janett, Caro Lozano; Teresa, Reyes Gabino Patricia; Ulises, Lozano Gómez; Leobardo, Ureña BogarínEnrique (International Journal of Innovative Research in Medical Science, 2017)
“NASH (Non-alcoholic steato hepatits) disease and metabolic syndrome in Mexico´s southeastern population Introduction: The nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease associated with an accumulation of fat that can lead to steatosis, steatohepatitis, cirrhosis, carcinoma and in cases more severe end-stage liver failure. The prevalence of this disease is unknown in the Mexican population; they have reported recent studies where it occurs up to 30% of the general population, being more frequent in subjects with central obesity, insulin resistance, hypertension and dyslipidemia, considered as criteria for diagnosis of metabolic syndrome (MS). Nonalcoholic fatty liver is the only hepatic manifestation of the metabolic syndrome. Materials and methods: This is a descriptive study in which subjects with an ultrasonography report of NASH were admitted, integrating cases with metabolic syndrome as its prevalence variable confirmed by at least 3 different diagnostic criteria for MS. Staging and categorization of MS and NASH components were ensamble as well a determine the differences between Chi-square test and Anova of a factor according to the variable, the correlation level between these was determined by the Spearman test. Results: A population of 200 patients were included with an ultrasonography diagnosis of NASH, 39% with Metabolic Syndrome (MS) criteria. 7 out of 10 patients with MS presented mild steatosis with a correlation value of 54.4% in female patients and 45.5% in male patients, reporting a male/female trust interval ratio of 0.989 (Trust interval ratio to 95% (IC95%):33.7 - 46.2)). As well a correlation between obese patients and steatohepatic disease stages was made, getting a Rho: 0.11 value.